Serum retinol binding protein as a novel marker for clearance and dosage optimization: pharmacokinetics study of voriconazole in a cirrhosis population - Yun, Juping; Bai, Haihong; Wang, Zihe; Ma, Yingmin; Liu, Wei (Frontiers in Pharmacology, 2025)
Background and ObjectiveVoriconazole (VRC) exhibits nonlinear pharmacokinetic (PK) characteristics and a narrow therapeutic window. Consequently, standardized dosage regimens are insufficient to achieve the targeted therapeutic exposure in patients with cirrhosis. While numerous population pharmacokinetic (PPK) studies on VRC have been conducted, data on the cirrhosis demographic remain limited.This study aimed to explore the PK characteristics of VRC and its covariates in a cirrhosis population, with the objective of recommending individualized dosing regimens.MethodsData collected from routine therapeutic drug monitoring (TDM) of patients with recorded VRC plasma concentrations during a period of therapy between September 2022 and August 2024 were included. A population pharmacokinetic (PPK) model was constructed using nonlinear mixed-effects modeling (NONMEM). Monte Carlo simulation was used to predict the target trough concentrations of VRC under steady-state conditions based on the final model parameters, thereby facilitating tailored dosage recommendations.ResultsA total of 151 trough concentrations were obtained from 78 patients enrolled in the PPK study of VRC. A one-compartment model featuring first-order absorption and first-order elimination was optimal in describing the PK characteristics, additionally incorporating Child-Pugh grades and retinol-binding protein (RBP) as covariates affecting the central ventricular clearance rate (CL) of VRC. In the final model, the CL was determined as 6.96 L/h. For patients classified as Child-Pugh A and B with RBP ≥25 mg/L, the recommended dosages were 400 mg/d and 200 mg/d, respectively. At RBP levels <25 mg/L, the recommended dosages for Child-Pugh A and C patients were 200 mg/d and 100 mg/d, respectively, while for Child-Pugh B patients, both 200 mg/d and 100 mg/d were recommended.ConclusionOur results support the utility of RBP as a novel marker associated with VRC clearance. This biomarker may offer a practical option for VRC dosage optimization. The clinical dosage of VRC could be tailored according to the Child-Pugh grades and RBP levels of patients. While numerous unexplained factors potentially influence the pharmacokinetic properties of VRC, the application of PPK model-guided TDM is crucial for achieving precision in individualized medication regimens.